2008
DOI: 10.1590/s0004-282x2008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Neurological outcome of newborns with neonatal seizures: a cohort study in a tertiary university hospital

Abstract: -Objective: To describe the neurological outcome of newborns with seizures. Method: Cohort study with newborns prospectively followed. Perinatal characteristics and etiological screening were related to outcome in a regression model. Results: During the study 3659 newborns were admitted and 2.7% were diagnosed as having seizures. Hypoxic ischemic encephalopathy (51%) was the etiology more frequently associated to seizures and also to postneonatal epilepsy (53%). In the follow up 25 died during the acute neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 27 publications
6
33
1
1
Order By: Relevance
“…Many studies reported male preponderance among babies with seizures [5][6][7][8][9][10][11]. This is in keeping with male to female ratio of 2.9:1 reported in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many studies reported male preponderance among babies with seizures [5][6][7][8][9][10][11]. This is in keeping with male to female ratio of 2.9:1 reported in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Reports from developing countries though mostly hospital based [4][5][6][7][8] signify a high incidence of neonatal morbidity including seizures compared to that from developed countries [9][10][11]. Unfortunately, in most centers in developing countries where neonatal seizures as well as newborn morbidity and mortality are high, facilities to fully investigate, monitor and manage neonatal seizures are often inadequate [4][5][6][7][8].…”
Section: Introduction mentioning
confidence: 99%
“…11. Hypoxic-ischaemic encephalopathy [55–57], CNS damage [58, 59], epilepsy [60, 61], nephropathy [43], cardiomyopathy [62, 63], vascular pathologies [64], senescence [32, 65], diabetes mellitus [66, 67], cancer [68], neurodegenerative diseases [58], morbidity and mortality [69] and tissue remodelling [70] all belong to individual short- and long-term outcomes of birth asphyxia. Specialised issue of The EPMA Journal , further treat the major related topics, namely “PPPM in Diabetes”, “PPPM in Neurodegenerative Diseases”, “PPPM in Cancer”, “PPPM in Cardiovascular Diseases”, “PPPM in Body Culture and Sport Medicine”, “Healthcare Overview”, where the articles overview the innovative technologies of predictive diagnostics, targeted prevention measures and desirable personalisation of medical care [7180].…”
Section: Central Biological Processes Affected By Perinatal Asphyxiamentioning
confidence: 99%
“…Although some epilepsy syndromes affecting children less than one of year of age can have favorable prognoses, others result in medically refractory seizures, developmental delay/intellectual disability, and other neurologic handicaps (Nunes, et al 2008, Yamamoto, et al 2011, van der Heide, et al 2012). While the increased morbidity of early onset epilepsy is known, its mortality has not been robustly explored.…”
Section: 1 Introductionmentioning
confidence: 99%